DIABETES KNOWLEDGE AND ASSOCIATED FACTORS AMONG OUTPATIENTS WITH TYPE 2 DIABETES MELLITUS (Vietnam Journal of Community Medicine, 2026)
Objective: This study uses the Vietnamese version of the DKQ-24 scale to survey the level of understanding of diabetes patients about the disease and related factors.Subjects and methods: A cross-sectional study was conducted on 273 outpatients with type 2 diabetes mellitus at Nguyen Trai Hospital, Ho Chi Minh city, from October 2024 to March 2025.Results: Among 273 patients, only 7% had adequate knowledge, and 33.7% achieved good HbA1c control. Significant associations were identified between DKQ-24 scores and diabetes duration (p < 0.001), living place (p = 0.036), educational status (p < 0.001), diet adherence (p = 0.013), physical exercise (p = 0.002), information sources (p = 0.001), and participate in diabetes education programs (p = 0.034). Patients proactively seeking reliable information and attending education programs had significantly higher DKQ-24 scores.Conclusion: Knowledge of type 2 diabetes mellitus is inadequate, emphasizing the need to promote access to reliable information and enhance education efforts.
Keywords: Type 2 diabetes mellitus, diabetes knowledge, DKQ-24.